Thoughts, beliefs and concepts concerning infectious childhood diseases of physicians practicing homeopathic, anthroposophic and conventional medicine - a qualitative study - N. Mittring-Junghans; C. Holmberg; C. M. Witt; M. Teut (BMC, 2021)
Abstract Background Physicians who include complementary medicine in their practice are thought to have an understanding of health and disease different from that of colleagues practicing conventional medicine. The aim of this study was to identify and compare the thoughts and concepts concerning infectious childhood diseases (measles, mumps, rubella, chickenpox, pertussis and scarlet fever) of physicians practicing homeopathic, anthroposophic and conventional medicine. Methods This qualitative study used semistructured interviews. Participating physicians were either general practitioners or pediatricians. Data collection and analysis were guided by a grounded theory approach. Results Eighteen physicians were interviewed (6 homeopathic, 6 anthroposophic and 6 conventional). All physicians agreed that while many classic infectious childhood diseases such as measles, mumps and rubella are rarely observed today, other diseases, such as chickenpox and scarlet fever, are still commonly diagnosed. All interviewed physicians vaccinated against childhood diseases. A core concern for physicians practicing conventional medicine was the risk of complications of the diseases. Therefore, it was considered essential for them to advise their patients to strictly follow the vaccination schedule. Homeopathic-oriented physicians viewed acute disease as a biological process necessary to strengthen health, fortify the immune system and increase resistance to chronic disease. They tended to treat infectious childhood diseases with homeopathic remedies and administered available vaccines as part of individual decision-making approaches with parents. For anthroposophic-oriented physicians, infectious childhood diseases were considered a crucial factor in the psychosocial growth of children. They tended to treat these diseases with anthroposophic medicine and underlined the importance of the family's resources. Informing parents about the potential benefits and risks of vaccination was considered important. All physicians agreed that parent-delivered loving care of a sick child could benefit the parent-child relationship. Additionally, all recognized that existing working conditions hindered parents from providing such care for longer durations of time. Conclusions The interviewed physicians agreed that vaccines are an important aspect of modern pediatrics. They differed in their approach regarding when and what to vaccinate against. The different conceptual understandings of infectious childhood diseases influenced this decision-making. A survey with a larger sample would be needed to verify these observations.